Evidence for improved patient management through electronic patient records at a Central Australian Aboriginal Health Service - Wendy E. Hoy; Cheryl E. Swanson; Alex Hope; Jo Smith; Chris Masters (Elsevier, 2014)
Abstract Aim: To examine chronic disease (CD)‐related clinical activity and outcomes associated with introduction of a more systematic approach to chronic disease care in a remote Aboriginal community, using data from Communicare patient record management system. Methods: We examined CD process measures, outcomes and clinical profiles in adults age 15+ years from Communicare data and compared results for two intervals. Process measures were clinic visits and proportions of eligible patients with recorded CD‐related procedures or diagnostic tests. Outcome measures were results of CD care items and CD morbidities. Data in the interval 2007-2009 were compared with data from 2009 to 2011, in which an intensified CD program was conducted in the clinic by its own staff. Results: About one‐third of adult visits were related to CD care; CD‐cycle of care encounters increased significantly in the second interval, from 3.2% to 9.1%, and proportions of adults having CD‐related procedures or tests were also higher. For already commonly performed items, like blood pressure, weight and lipids, proportions of adults tested were 30-50% higher in the second interval, while proportions tested for more recently emphasised items, like waist, HbA1C, urine ACR, rose by more than 200%. Levels of SBP, DBP, HbA1c and HDL‐C significantly improved in the second interval. Proportions of adults with clinical values outside normal ranges decreased for at least half of observations. Conclusions: Parameters of CD care activities and outcomes have increased significantly over the last four years in this setting, accompanied by stabilisation of or improvement in outcomes.